Leadership‐evaluation partnership: Infusing systems principles and complexity concepts for a transformational alliance. Issue 170 (1st September 2021) - Richardson, Ruth A.; Patton, Michael Q.
Abstract: The Global Alliance for the Future of Food provides a case exemplar of incorporating systems thinking, complexity understandings, and developmental evaluation into systems transformation work. This transformational engagement is not just rhetoric but is deeply embedded as the focus of the Global Alliance's ongoing work. It is, importantly, predicated on in‐depth and long‐term cocreation and collaboration between alliance leadership and an independent external evaluator. This chapter will tell the story of how the Global Alliance incorporated systems thinking, complexity understandings, and principles‐focused developmental evaluation into systems transformation work through the reflective practice of the coauthors, Ruth Richardson, the Global Alliance Executive Director, and Michael Quinn Patton, the developmental evaluation consultant to the Global Alliance.